2017
DOI: 10.1182/bloodadvances.2017008078
|View full text |Cite
|
Sign up to set email alerts
|

The severe phenotype of Diamond-Blackfan anemia is modulated by heat shock protein 70

Abstract: Key Points• Proteasomal HSP70 degradation results in cleavage of GATA1, decrease in erythroid progenitors, and apoptosis in severe DBA phenotype.• HSP70 plays a role not only during terminal erythroid differentiation, but also in the earlier proliferation of erythroid progenitor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 64 publications
0
56
0
Order By: Relevance
“…This GATA1 protective mechanism appears to break down in hematological disorders manifesting with IE, such as DBA and MDS. In DBA, it was recently shown that HSP70 protein is downregulated due to its increased ubiquitination and proteasomal degradation in RPL11‐ and RPL5‐deficient human primary erythroid cells, but not in RPS19‐deficient cells, resulting in proliferation and differentiation defects and increased apoptosis in erythroid cells, resembling DBA features . A subsequent study showed a disequilibrium of globin chain and heme synthesis in RPL11‐ and RPL5‐deficient human erythroid cells, resulting in excessive free heme which downregulated HSP70 protein .…”
Section: Downregulation Of Gata1 Protein Levels and Ineffective Erythmentioning
confidence: 97%
See 1 more Smart Citation
“…This GATA1 protective mechanism appears to break down in hematological disorders manifesting with IE, such as DBA and MDS. In DBA, it was recently shown that HSP70 protein is downregulated due to its increased ubiquitination and proteasomal degradation in RPL11‐ and RPL5‐deficient human primary erythroid cells, but not in RPS19‐deficient cells, resulting in proliferation and differentiation defects and increased apoptosis in erythroid cells, resembling DBA features . A subsequent study showed a disequilibrium of globin chain and heme synthesis in RPL11‐ and RPL5‐deficient human erythroid cells, resulting in excessive free heme which downregulated HSP70 protein .…”
Section: Downregulation Of Gata1 Protein Levels and Ineffective Erythmentioning
confidence: 97%
“…The study by Doty et al also suggests that aberrant accumulation of heme, contributes to the amplification of RP imbalance, thus causing premature downregulation of GATA1 levels, responsible for the IE that is characteristic of DBA and MDS . Hence, it is clear in that in DBA, HSP70 downregulation results in a significant drop in GATA1 protein levels due to caspase‐mediated cleavage, which underlies the observed erythroid maturation defects . The HSP70 mediated protection of GATA1 is also disrupted in β‐thalassemia, which also manifests with IE.…”
Section: Downregulation Of Gata1 Protein Levels and Ineffective Erythmentioning
confidence: 99%
“…Ludwig et al 53 have shown that GATA1 transcripts are specifically less translated compared to others in DBA owing to a higher threshold for initiation of translation of GATA1 mRNA due to defective ribosomal biogenesis. Gastou et al 54 showed that HSP70, the chaperon of GATA1, is degraded by the proteasome following polyubiquitination during the BFU-E and CFU-E stages of erythropoiesis. Decreased HSP70 expression has been noted in all of the RP mutated-gene-tested DBA patients and in shRNA models other than RPS19, which exhibit a normal expression of HSP70.…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…This correlates perfectly with the low level of induced apoptosis in these RPS19-mutated DBA patients compared to the RPL5- or RPL11-mutated ones. Interestingly, HSP70 degradation is responsible for caspase-3-dependent GATA1 cleavage during terminal erythroid differentiation and the resultant decreased GATA1 protein expression at late stages of erythroid differentiation 54 . Finally, the EPO gene has been found to be mutated in one consanguineous Turkish family in the USA, with a homozygous missense mutation in exon 5 of EPO .…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…Two recent papers suggest that decrease of GATA1 full-length protein resulting from RP haploinsufficiency and deficiency of HSP70 can disturb the balance of globin-heme and leads to the accumulation of free cytoplasmic heme in erythroid progenitors, which can cause increase of P53-dependent apoptosis of DBA erythroid cells. [119][120][121] Of note, unlike in the presence of RP mutations in DBA patients, accumulation of heme upon only FLVCR1 depletion causes P53-independent apoptosis. 120 Finally, work by Bodine and colleagues suggest yet another model for pathogenesis of DBA.…”
Section: Gata1 Mutations In Dbamentioning
confidence: 99%